Carvone and its eutectic mixtures as novel, biodegradable, and tunable solvents to extract hydrophobic compounds in substitution for volatile toxic solvents. (16th April 2022) - Li, Ke; Nam, Jin Hyun; Kang, Seulgi; Liu, Yuli; Lee, Jeongmi
Highlights: Carvone is a new bio-based source of water-immiscible hydrophobic solvent. Carvone eutectic mixtures have a wide liquid window with low viscosity. COSMO-RS calculation with machine learning can reasonably classify solvents. Carvone eutectic mixtures are green substitutes for polar protic and dipolar aprotic solvents. Carvone eutectic mixtures are designer solvents for extraction of hydrophobic compounds. Abstract: Finding safe solvents with low viscosities has been in great demand in extraction processes. Herein, R-(-)-carvone, a natural monoterpenoid rich in spearmint, was mixed with naturally occurring fatty acids and terpenes. Most eutectic mixtures presented a wide liquid window in the solid-liquid equilibrium phase diagrams. Carvone mixtures at the ideal eutectic points were characterized for physicochemical properties. Despite varying properties, all the tested solvents were immiscible with water and displayed low viscosity with reasonable biodegradability. Sigma potentials of the mixtures were applied to machine learning algorithms, suggesting carvone mixtures as substitutes for polar protic and dipolar aprotic solvents. Carvone mixtures could be successfully applied to liquid-liquid extraction of a red algae called laver, which is rich in natural hydrophobic and hydrophilic pigments of high value. This study proposes carvone as a new bio-based source of hydrophobic solvents and the eutectic mixtures as biodegradable and tunable solvents to extract hydrophobic compounds.